IDENTIFICATION OF PREGNANT MOTHER'S ANXIETY DURING THE COVID-19 PANDEMIC IN THE AREA OF KALAMPANGAN COMMUNITY HEALTH CENTER - Anita Sunjaya; Oktaviani Oktaviani; Seri Wahyuni (POLTEKKES KEMENKES JAYAPURA, 2022)
The decrease in visits by pregnant women to check themselves is closely related to the anxiety and fear of pregnant women during the Covid-19 pandemic. Worries due to the risk of contracting Covid-19 have caused mothers to delay their pregnancy check-ups at basic service facilities or primary health care other health care facilities. The lack of services in terms of personnel and infrastructure, including personal protective equipment, also has an impact on anxiety for pregnant women. The purpose of the study was to identify the anxiety of pregnant women during the Covid-19 pandemic in the work area of ​​the Kalampangan Health Center. The research design was cross-sectional, with a sample of 133 pregnant women in the third trimester who performed Ante Natal Care in the Work Area of ​​the Kalampangan Health Center. The significant relationship between age and anxiety of pregnant women (p-value = 0.002), parity with anxiety of pregnant women (p-value = 0.002), and education with the anxiety of pregnant women (p-value = 0.003), work status, and marital status were not related. significantly with the incidence of the anxiety/fear in pregnant women. Pregnant women should avoid anxiety by increasing their knowledge so that anxiety can be managed properly. Knowledge of pregnant women can be increased through counseling, counseling, online classes, and home visits. Keywords: Pregnant women, Anxiety, Covid-19 pandemic